2021
DOI: 10.1038/s41531-021-00174-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-motor predictors of 36-month quality of life after subthalamic stimulation in Parkinson disease

Abstract: To identify predictors of 36-month follow-up quality of life (QoL) outcome after bilateral subthalamic nucleus deep brain stimulation (STN-DBS) in Parkinson’s disease (PD). In this ongoing, prospective, multicenter international study (Cologne, Manchester, London) including 73 patients undergoing STN-DBS, we assessed the following scales preoperatively and at 6-month and 36-month follow-up: PD Questionnaire-8 (PDQ-8), NMSScale (NMSS), Scales for Outcomes in PD (SCOPA)-motor examination, -activities of daily li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 40 publications
1
20
1
Order By: Relevance
“…Awareness of the progression of these symptoms in clinical practice, with the aim to introduce interventions to reduce NMS burden progression when possible, could be important. As example, bilateral subthalamic stimulation (STN-DBS) improved significantly the global SNMS burden and QoL in advanced PD patients after 36 months but not in patients who received the standard-of-care medical therapy [ 19 ]. Since global NMS burden impacts the patient’s QoL [ 8 ] and its progression worsens QoL [ 13 ], understanding the role global NMS plays in PD is very relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of the progression of these symptoms in clinical practice, with the aim to introduce interventions to reduce NMS burden progression when possible, could be important. As example, bilateral subthalamic stimulation (STN-DBS) improved significantly the global SNMS burden and QoL in advanced PD patients after 36 months but not in patients who received the standard-of-care medical therapy [ 19 ]. Since global NMS burden impacts the patient’s QoL [ 8 ] and its progression worsens QoL [ 13 ], understanding the role global NMS plays in PD is very relevant.…”
Section: Discussionmentioning
confidence: 99%
“…54 Motor as well as nonmotor symptoms contribute to QoL. 55,56 It has been shown that nonmotor symptoms are even strongly correlated to QoL than motor symptoms 18,57 QoL 56 EARLYSTIM did not assess nonmotor symptoms with an adequate scale 58 as this was not yet available at the time of the study planning. However, having detailed data on these aspects would possibly help explain a larger part of the QoL changes and thereby might better help explain the sweet spot relations.…”
Section: Limitationsmentioning
confidence: 99%
“…Better understanding of the STN itself can lead to more stable motor improvements as well [11]. Moreover, increasing insights in the clinical non-motor characteristics, genetic profiles, and neurophysiological characteristics and their relation with DBS outcome have promising potential to improve patient selection, counseling, and outcome prediction [18,42]. All these approaches do not exclude each other and can improve DBS outcome in PD in a complementary way in the future.…”
Section: Alternative Approaches For Preoperative Stn Dbs Outcome Impr...mentioning
confidence: 99%